Implementation of Copyright in Intellectual Property Law As A Credit Guarantee Object in Banks based on Government Regulation No. 24 of 2022 - Abdillah, Rezha Zulfikar (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
Copyright as part of intellectual property law has an important role in supporting innovation and creativity. This article discusses the implementation of copyright as an object of credit collateral at banks. This research aims to analyze the mechanism for using copyright in banking transactions, as well as identifying obstacles and solutions that may arise. The research method used is literature study and normative legal analysis. The research results show that although copyright can be used as credit collateral, its implementation still faces various challenges, such as assessing the economic value of copyright and a lack of understanding from banks. This research also provides recommendations for increasing the use of copyright as an object of credit collateral, including the need for clearer regulations and increased outreach to related parties. In this way, it is hoped that a more effective and efficient system can be created in the use of copyright as credit collateral in Indonesia.